A European Consensus on the Consistent Use of the Term "Keratinocyte Cancer" - Wolfgang G. Philipp-Dormston; Lasse R. Braathen; Colin A. Morton; Merete Haedersdal; Yolanda Gilaberte; Nicole Basset-Seguin; Elena Sotiriou; Stine Regin Wiegell; Piergiacomo Calzavara-Pinton; Thomas Dirschka; Hans Christian Wulf; Günther Hofbauer; et al. (Medical Journals Sweden, 2024)
Keratinocyte-derived skin cancers comprise basal cell carcinoma, squamous cell carcinoma, its precursor actinic keratosis, and Bowen's disease. Historically, this group of neoplasms has been subsumed under the term non-melanoma skin cancer. However, the term non-melanoma skin cancer can be misleading and lacks precision. Therefore, more precise and reasonable terminology, valuing the relevance of keratinocyte-derived cancer, appears pertinent to meet its clinical and scientific significance. A group of experienced dermato-oncologists initiated a consensus approach to promote the use of the term "keratinocyte cancer" instead of "non-melanoma skin cancer" when referring to carcinomas and their precursors that are derived from keratinocytes. The vote among members of the consensus group indicated unanimous agreement on the consistent use of the term "keratinocyte cancer" instead of "non-melanoma skin cancer". International delegates also voted in favour of the revised terminology. The more precise and, by means of etiopathogenesis, correct term "keratinocyte cancer" should be consistently used for malignancies originated from keratinocytes. This is expected to have a positive impact on patient-physician communication and gives better justice to this important group of keratinocyte-derived cancers.